Comparison of carbohydrate compositions of total apolipoproteins in lipoproteins - Güldür, T; Ozan, S; Ileri, T (Scientific Technical Research Council Turkey, 1999)
Terminal carbohydrate moieties of apolipoproteins of lipoproteins in human and goat serum were ascertained and compared. Apolipoproteins of beta+pre-beta (apolipoprotein B containing lipoproteins) and alpha lipoproteins separated by phosphotungstic acid/MgCl2 precipitation method were applied to SDS-PAGE and blotted onto nitrocellulose membrane. Digoxigenin labelled lectins, each of which recognizes a specific sugar sequence, were incubated with apolipoproteins immobilized on a western blot membrane to probe some of carbohydrate structures commonly found in carbohydrate chains of glycoproteins. The presence of bound lectin on the membrane was detected with alkaline phosphatase labelled antidigoxigenin antibody. Sialic acid terminally linked alpha (2-->3) to galactose was detected on the largest protein band in beta+pre-beta lipoprotein fraction of both human and goat serum with the mobility identical to that of apo B. Neither of the carbohydrate moieties probed were found to be present in alpha lipoproteins.
Lipoproteinlerin Total Apolipoproteinlerinin Karbohidrat Kompozisyonlarinin Karşilaştirilmasi
Keywords: lipoprotein; apolipoprotein; carbohydrate moiety